Clinical Epidemiology of Stroke in the Productive Age Population in Indonesia: a Scoping Review - Asmara, Satria Akbar Putra; Habibah, Ulil Albab (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
Data from the 2018 Indonesian Basic Health Research (Riskesdas) demonstrates a marked increase in stroke prevalence, rising from 7% in 2013 to 10% in 2018. This upward trend is accompanied by a notable epidemiological shift, with stroke no longer predominantly affecting older adults ≥65 years, but increasingly occurring among the productive-age population (15–64 years). This scoping review was conducted in February 2026 in accordance with the JBI methodological guidelines and PRISMA-ScR. Searches were conducted in Google Scholar, PubMed, Garuda, and ScienceDirect. Inclusion criteria include articles published within the last 10 years (2016–2026), articles discussing the characteristics of stroke patients in the productive age group in Indonesia, observational studies, and articles published in English or Indonesian. Data extraction includes author, year of publication, study design, location, sample size, age range, and main findings. Six studies met the inclusion criteria. Ischemic stroke was the predominant subtype, and most young stroke patients in Indonesia were male. The majority of patients had a history of hypertension, hyperlipidemia, gout, and diabetes mellitus. Stroke in the productive age in Indonesia, predominantly ischemic, shows an increasing trend with age (18–59 years) and a higher prevalence in males, though housewives emerge as a highly vulnerable female subgroup. Patients exhibit heterogeneous BMI profiles clustering with a high descriptive prevalence of metabolic comorbidities. Given the reliance on six hospital-based descriptive studies, these findings represent preliminary regional trends rather than a definitive national profile, emphasizing the urgent need for a centralized national stroke registry and future community-based analytical studies. Keywords: Productive age, Stroke, Indonesia